An investigation into the clinical reasoning development of veterinary students - Vinten, Claire; Cobb, Kate A.; Freeman, S.L.; Mossop, Liz (University of Toronto Press, 2016)
Clinical reasoning is a fundamental skill for veterinary clinicians and a competency required of graduates by the Royal College of Veterinary Surgeons. However, it is unknown how veterinary students develop reasoning skills and where strengths and shortcomings of curricula lie. This research aimed to use the University of Nottingham School of Veterinary Medicine and Science (SVMS) as a case study to investigate the development of clinical reasoning among veterinary students. The analysis was framed in consideration of the taught, learned, and declared curricula. Sixteen staff and sixteen students from the SVMS participated separately in a total of four focus groups. In addition, five interviews were conducted with recent SVMS graduates. Audio transcriptions were used to conduct a thematic analysis. A content analysis was performed on all curriculum documentation. It was found that SVMS graduates feel they have a good level of reasoning ability, but they still experience a deficit in their reasoning capabilities when starting their first job. Overarching themes arising from the data suggest that a lack of responsibility for clinical decisions during the program and the embedded nature of the clinical reasoning skill within the curriculum could be restricting development. In addition, SVMS students would benefit from clinical reasoning training where factors influencing ‘‘real life’’ decisions (e.g., finances) are explored in more depth. Integrating these factors into the curriculum could lead to improved decision-making ability among SVMS graduates and better prepare students for the stressful transition to practice. These findings are likely to have implications for other veterinary curricula.